Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1).x:2+x:3=5/2
=>x.1/2+x.1/3=5/2
=>x(1/2+1/3)=5/2
=>x.5/6=5/2
=>x=5/2:5/6
=>x=3
<=> 1+\(\frac{1}{2014}\)+\(\frac{1}{x}\)=\(\frac{1}{x+1}\)+1+\(\frac{1}{2013}\)
<=> \(\frac{1}{2014}\)+\(\frac{1}{x}\)=\(\frac{1}{x+1}\)+\(\frac{1}{2013}\)
<=> \(\frac{1}{x}\)-\(\frac{1}{x+1}\)=\(\frac{1}{2013}\)-\(\frac{1}{2013+1}\) => x=2013
\(\frac{2015}{2014}+\frac{1}{x}=\frac{1}{x+1}+\frac{2014}{2013}\)
\(\Leftrightarrow\frac{2015}{2014}-1+\frac{1}{x}=\frac{1}{x+1}+\frac{2014}{2013}-1\)
\(\Leftrightarrow\frac{1}{2014}+\frac{1}{x}=\frac{1}{x+1}+\frac{1}{2013}\)
\(\Leftrightarrow\frac{x+2014}{2014x}=\frac{x+2014}{2013\left(x+1\right)}\)
\(\Leftrightarrow2014x=2013x+2013\)
\(\Leftrightarrow x=2013\)